Philosophical Content in Small Lyrical forms of Sirojiddin Sayyid (On the example of S.Sayyid's collection of poems "Kungil sokhili") (Eurasian Journal of Learning and Academic Teaching, 2023)
This article analyzes the lyrical poems of Sirajaddin Sayid, the peculiarities of his philosophical thoughts in his quatrains.